Coiling of a Postinterventional Pseudoaneurysm After Distal Locking of a Proximal Femoral Nail - Rahimov, Elvin; Viera, Julio; Vieth, Volker; Müller, Marcus Christian (Zeitschrift für Orthopädie und Unfallchirurgie, 2024)
Pertrochanteric femoral fractures are among the most common injuries in geriatric patients. Intramedullary implants are used to restore patient mobility. We report coil embolisation of an aneurysma spurium of the profunda femoral artery as a complication after distal nail locking of a proximal femoral nail.
Keywords: aneurysma spurium; proximal femoral nail; pertrochanteric femoral fracture; digital subtraction angiography; coil embolization